2012
DOI: 10.1002/jso.23281
|View full text |Cite
|
Sign up to set email alerts
|

Increased PD‐1 expression on CD4+ and CD8+ T cells is involved in immune evasion in gastric cancer

Abstract: Upregulation of PD-1 on both CD4+ and CD8+ T cells may be, in part, responsible for immune evasion in gastric cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 38 publications
4
64
0
1
Order By: Relevance
“…and CD8 ? T cells was involved in immune evasion [15]. Another study examined PD-L1, cytotoxic T-lymphocyte-associated antigen 4, and indolamine 2,3-dioxygenase expression by immunohistochemistry, and showed that PD-L1 positivity and a high-CD3 microenvironment were related to favorable survival outcomes [14].…”
Section: Discussionmentioning
confidence: 99%
“…and CD8 ? T cells was involved in immune evasion [15]. Another study examined PD-L1, cytotoxic T-lymphocyte-associated antigen 4, and indolamine 2,3-dioxygenase expression by immunohistochemistry, and showed that PD-L1 positivity and a high-CD3 microenvironment were related to favorable survival outcomes [14].…”
Section: Discussionmentioning
confidence: 99%
“…28 In recent years, a number of studies confirmed PD-L1 expression on the surface of gastric cancer cells 29,30 ; PD-1 expression in peripheral circulating blood lymphocytes, tumor-infiltrating lymphocytes, and its ligands; and PD-L1 in serum and tumor tissue. 31 The expression of PD-L1 and PD-1 was closely related with tumor progression, invasion, …”
Section: Discussionmentioning
confidence: 99%
“…Preclinical and translational studies suggest that PD-1 may be an important and promising therapy in gastric cancers, as gastric cancers and infiltrating T cells have higher levels of PD-1 and PD-L1 than adjacent non-tumorous gastric tissue, and the peripheral blood (35). This buttresses the hypothesis that tumor expression of PD-L-1 may result in the recruitment of T cells, and their subsequent persistent activation and exhaustion, perhaps contributing to carcinogenesis and progression.…”
Section: Checkpoint Inhibitorsmentioning
confidence: 84%
“…While there was no clear difference in outcomes between the two treatment arms in the primary endpoint, progression free survival or objective response rate, there was a significant difference in overall survival, favoring paclitaxel/olaparib, both in the overall population (HR =0.56), and in particular in the low ATM population (HR =0. 35). This has led to the development of a phase III study in patients with low ATM expression gastric cancers (43).…”
Section: Ataxia Telangiectasia Mutated (Atm)mentioning
confidence: 99%